New Medium for Blood Cultures - Morello, Josephine A. (1969)
A new medium suitable for blood cultures is described. It contains dextrose, cysteine, iron, and magnesium, in a tris(hydroxymethyl)aminomethane buffer, and a mixture of peptones derived from animal tissues, casein, and yeast. In comparison with Trypticase Soy Broth, the growth rate constants of Staphylococcus aureus, Streptococcus (Viridans group), enterococcus, and Escherichia coli were higher in this medium, and growth appeared earlier in a significant number of clinical blood cultures.